2016
DOI: 10.5301/jabfm.5000294
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Physical Properties of a Nanocomposite after Aging, Bleaching and Staining

Abstract: The bleaching reduced the microhardness of the nanocomposite, whereas the aging process changed all the properties studied. The bleaching favored extrinsic staining of the with aging nanocomposite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 36 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…Natrosol (hidroxietilcelulose) is a cellulose-based polymer and differs from carbopol mainly due to its nonionic nature. [ 7 ] In addition, natrosol can be associated to acidic substances in whitening gels, due to its remarkable stability to pH variation (2.0–12.0). Carbopol, in turn, a thickener commonly used in at-home bleaching gels,[ 7 ] is a carboxypolymethylene polymer, ionic and acidic in nature, being a carboxylic acid derivative.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Natrosol (hidroxietilcelulose) is a cellulose-based polymer and differs from carbopol mainly due to its nonionic nature. [ 7 ] In addition, natrosol can be associated to acidic substances in whitening gels, due to its remarkable stability to pH variation (2.0–12.0). Carbopol, in turn, a thickener commonly used in at-home bleaching gels,[ 7 ] is a carboxypolymethylene polymer, ionic and acidic in nature, being a carboxylic acid derivative.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] In addition, natrosol can be associated to acidic substances in whitening gels, due to its remarkable stability to pH variation (2.0–12.0). Carbopol, in turn, a thickener commonly used in at-home bleaching gels,[ 7 ] is a carboxypolymethylene polymer, ionic and acidic in nature, being a carboxylic acid derivative. Due to its strong calcium-binding ability,[ 8 ] it has been reported that carbopol can reduce enamel microhardness and dentin since it causes inhibition of hydroxyapatite crystal incorporation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although remineralization actions are not expected in the composite resin, the purpose of using RS was to simulate the oral environment. 27 …”
Section: Brushing Protocolmentioning
confidence: 99%
“…Among the adverse effects reported, the following are noteworthy: I) increased permeability and changes in the roughness and topography of the enamel (Camargo et al, 2007;Hosoya et al, 2003;Llena, Esteve, Forner, 2017;Markovic et al, 2007;Vieira-Junior et al, 2018); II) decrease surface and cross-sectional microhardness (Al-Salehi, Wood, Hatton, 2007;Berger et al, 2010;Cavalli et al, 2018); III) surface changes visualized in a Scanning Electron Microscopy (D'Amario et al, 2012;Grazioli et al, 2018;Vieira-Junior et al, 2018); IV) dissolution of calcium, phosphorus, and fluorine of the dental hydroxyapatite crystal for the whitening gel (Al-Salehi, Wood, Hatton, 2007;Cavalli et al, 2018;Vieira-Junior et al, 2018); V) changes in properties of resin-based restorative materials (Gouveia et al, 2016;Gouveia et al, 2006;Telang et al, 2018); VI) alteration in the bond strength of dental substrates by restorative materials (Lima et al, 2011;Miranda et al, 2013).…”
Section: Undesirable Effects Of Conventional Bleachingmentioning
confidence: 99%